Dodecatungstophosphoric acid supported on acidic clay catalyst for disproportionation of ethylbenzene in the presence of C-8 aromatics - Bokade, Vijay V.; Yadav, Ganapati D. (Industrial & Engineering Chemistry Research, 2012)
Vapor-phase disproportionation of ethylbenzene (EB) to diethylbenzene (DEB) in a single step is industrially relevant. Diethylbenzene is an important raw material for the conversion of divinylbenzene monomer. Conventionally, it is prepared from diacetophenone by reduction. It is also prepared by vapor-phase alkylation of ethylbenzene with ethylene/ethanol using zeolitic catalysts. In the current work, the efficacy of dodecatungstophosphoric acid (DTPA) supported on acid-treated clay has been evaluated in the disproportionation of ethylbenzene. A 20% (w/w) DTPA/K-10 clay catalyst was found to be efficient and robust. An industrial feed having different compositions of ethylbenzene and xylene isomers was used for the experimentation. Hence, they were expected to hinder the movement of reactant molecules on the catalyst surface. It was observed that irrespective of feed composition the concentration of the xylene isomers was intact in the product. There was no other byproduct formation like p-ethylrnethylbenzene. Optimization of process parameters is presented. The effect of varying the concentration of aromatic compounds in the feed on ethylbenzene conversion and product distribution over the plain clay (K-10) and heteropolyacid-loaded clay catalyst have been discussed. The effect of catalyst bed length to inner diameter of reactor (L/D) ratio on the ethylbenzene conversion and selective formation of p-diethylbenzene (p-DEB) are also discussed.